Association of Vitamin D Deficiency with Gestational Diabetes - Sattar, Qandil; Syed, Wajeeha (Indus Journal of Bioscience Research, 2025)
Background: A common illness that presents serious risks to the mother and foetus is gestational diabetes mellitus. The hypothesis suggests that vitamin D insufficiency may serve as an etiological element in the development of gestational diabetes mellitus (GDM). The scope of its influence upon demographic and clinical parameters, including age, parity, and gestational age, remains undefined. Objective: To determine the association of vitamin D deficiency with gestational diabetes. Design of the study: The study utilized a case-control design. Setting and Study Duration: The study was conducted from July 2024 to January 2025 at the Obstetrics and Gynaecology Department of Lady Reading Hospital, Peshawar. Methodology: 107 women with a diagnosis of gestational diabetes mellitus (case group) and 107 healthy controls were among the 214 women between the ages of 18 and 40 who took part of the study. We measured serum vitamin D levels and administered an oral glucose tolerance test to all patients between weeks 24 and 28 of pregnancy. Results: The study found that the GDM cohort's vitamin D levels were significantly lower than those of the control group. In the GDM group, the mean vitamin D level was 24.04 ± 9.23 nmol/L, while in the non-GDM sample, it was 39.16 ± 11.26 nmol/L (p < 0.000). The coefficient of regression of -10.024 (p < 0.001) indicated that being a member of the case group was associated with a significant decrease in vitamin D levels, according to multivariate analysis. Conclusion: The study discovered a strong correlation between vitamin D deficiency and an increased risk of gestational diabetes mellitus.